In vitro to in vivo extrapolation for high throughput prioritization and decision making. (March 2018) - Bell, Shannon M.; Chang, Xiaoqing; Wambaugh, John F.; Allen, David G.; Bartels, Mike; Brouwer, Kim L.R.; Casey, Warren M.; Choksi, Neepa; Ferguson, Stephen S.; Fraczkiewicz, Grazyna; Jarabek, Annie M.; Ke, Alice; et al.
Abstract: In vitro chemical safety testing methods offer the potential for efficient and economical tools to provide relevant assessments of human health risk. To realize this potential, methods are needed to relate in vitro effects to in vivo responses, i.e., in vitro to in vivo extrapolation (IVIVE). Currently available IVIVE approaches need to be refined before they can be utilized for regulatory decision-making. To explore the capabilities and limitations of IVIVE within this context, the U.S. Environmental Protection Agency Office of Research and Development and the National Toxicology Program Interagency Center for the Evaluation of Alternative Toxicological Methods co-organized a workshop and webinar series. Here, we integrate content from the webinars and workshop to discuss activities and resources that would promote inclusion of IVIVE in regulatory decision-making. We discuss properties of models that successfully generate predictions of in vivo doses from effective in vitro concentration, including the experimental systems that provide input parameters for these models, areas of success, and areas for improvement to reduce model uncertainty. Finally, we provide case studies on the uses of IVIVE in safety assessments, which highlight the respective differences, information requirements, and outcomes across various approaches when applied for decision-making. Highlights: In vitro to in vivo extrapolation uses a model relating active in vitro concentrations to an in vivo response-inducing dose Models for regulatory use will vary depending on needs: prioritization vs. hazard assessment Transparency and reporting standards for models are critical during implementation